1989
DOI: 10.1143/jjap.28.2074
|View full text |Cite
|
Sign up to set email alerts
|

Ta/SiN-Structure X-Ray Masks for Sub-Half-Micron LSIs

Abstract: In the subtractive X-ray mask fabrication process, suppressing distortions introduced in the bulk-Si etching step is of the utmost importance. Influences of absorber and membrane stresses on mask distortions were investigated in order to obtain good position accuracy. The required stress conditions in order to suppress absorber- and membrane-stress-induced distortions are <2×108 dyn/cm2 for Ta, and <5×108 dyn/cm2 for SiN with a thickness of 2 µm. A five-level mask-to-mask overlay accuracy of <0.085 µm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…2,3 For application of the x-ray mask to device fabrication, the number of defects must be reduced to zero. 2,3 For application of the x-ray mask to device fabrication, the number of defects must be reduced to zero.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 For application of the x-ray mask to device fabrication, the number of defects must be reduced to zero. 2,3 For application of the x-ray mask to device fabrication, the number of defects must be reduced to zero.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] For example, use of a thick silicon substrate, 9 backetching after rigid frame mounting, 10 and reducing the absorber stress gradient 11 can all reduce the distortion caused during mask fabrication. Pattern placement is affected by many factors, such as electron beam writing accuracy, membrane and absorber stresses, and mask fabrication method.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] The 512 kilobit static random access memory ͑SRAM͒ fabrication with 100% bit yield by IBM's group in 1993, for example, demonstrated that SR lithography was a viable candidate for sub-0.25 m device fabrication. 9 As the result of the development of SR rings, [11][12][13] x-ray steppers, 14 -18 high-quality x-ray masks, 19,20 and mask inspection 21 and repair 22 systems over the last decade, an infrastructure for SR lithography is now complete.…”
Section: Introductionmentioning
confidence: 99%